Intertidal foraging by Tristan Thrushes. (4th May 2019) - Ryan, Peter G; Dilley, Ben J
Abstract : We report that some 10% of Tristan Thrushes Turdus eremita on the coast at Inaccessible Island feed extensively on marine invertebrates (mainly crustaceans), despite lacking functional salt glands. Such birds regularly drink from freshwater springs that are common along the coast, but thrushes also forage along the coast at nearby Nightingale Island where there is little freshwater. One individual was observed feeding on stranded by-the-wind-sailors Velella velella . This appears to be only the second record of a passerine feeding on a cnidarian. These records further emphasise the resourcefulness of island birds in general, and the Tristan Thrush in particular, to exploit a wide range of food resources.